ANALISIS PROSEDUR ADMINISTRASI PENJUALAN TUNAI DAN KREDIT PADA PT SUN STAR MOTOR MALANG GUNA MENINGKATKAN PENGENDALIAN INTERN - Shinta Maharani Trivena; Rena Feri Wijayanti; Tri Yulistyawati Evelina (Politeknik Negeri Malang, 2019)
The purpose of this study was to determine the application of cash and credit sales administration at PT Sun Star Motor Malang in accordance with the existing Standard Operating Procedures. This type of research used in this study is a descriptive study with a qualitative approach. Data analysis techniques by finding and finding data, eliminating or reducing data, processing data, analyzing data, making conclusions and suggestions. The result is that the application of cash sales administration procedures at PT Sun Star Motor Malang is sometimes not in accordance with existing procedures. This is due to the accumulation of tasks performed by sales because of the quite important role of sales for consumers. If it is related to internal control, sales should not be able to accept cash because every sales transaction related to receiving cash is held by the cashier. Every receipt of money, both cash and non-cash from the buyer, will be made proof of receipt, for example receipts